Risk Analysis for Piping Systems Subject to Vibration Using Delphi Method - Zainul Asri, Muhammad Amir Syafiq (2018)
Many research, and studies has been done lately to discover and develop a systematic piping vibration risk assessment and those studies and experiments have their own specific ways of proving their judgements. However, piping vibration analysis and assessment is a complex subject and may not be easy to solve as expected by public. Delphi technique has been recognized for years as one of the qualitative approach to assist some researchers on their way of finding better solutions with the aid of the experts when there are insufficient amount of technical data and different observation of incidents in the similar event. Combination of some crucial facts research papers made by early predecessor to study the behavior of fluids movements and the cause of induced vibration are combined to provide reference for essential case study related to piping vibration analysis. Process pipe is the main transportation system connecting other system to another one and thus, it’s structure must be mechanically strong and flexible to handle the products or any other fluids passing through it. Severe failure of process pipe is just inevitable. However, some protection can be applied to reduce impact of unwanted forces that can lead to piping failure. A huge magnitude of vibration source can lead to a severe piping failure. Therefore, a structured risk analysis procedure related to piping vibration is carried out to assess the risk of piping failure dur to vibration. Methodological step of identifying the risk of the vibration occurrence in the process pipe is crucial prior risk evaluation and management could be done. Feedback from experts is the main components where it will be analyzed and ranked based on their risk level. This risk analysis research related to piping vibration will be conducted to industries nearby which has the most chances of having high risk of piping failure due to vibration.